Extra-uterine growth restriction in preterm infants: Neurodevelopmental outcomes according to different definitions. (July 2021) - De Rose, Domenico Umberto; Cota, Francesco; Gallini, Francesca; Bottoni, Anthea; Fabrizio, Giovanna Carmela; Ricci, Daniela; Romeo, Domenico Marco; Mercuri, Eugenio; Vento, Giovanni; Maggio, Luca
Abstract: Aim: Extra-uterine Growth Restriction (EUGR) is common among preterm infants. Two types of EUGR definitions are still now available: cross-sectional definitions and longitudinal ones. In a cohort of very preterm infants, we aimed to evaluate which definition could better predict neurodevelopmental outcomes at 2 years of corrected age. We used Italian Neonatal Study Charts (INeS) growth charts and INTERGROWTH-21st (IG-21) standard charts and compared results. Method: We restrospectively collected data from clinical charts of 324 preterm newborns with a gestational age ≤30 weeks born from 2012 to 2017. Then we compared forty-eight definitions (24 cross-sectional and 24 longitudinal) of EUGR, in term of neurodevelopmental outcomes at 2 years of corrected age. Results: We included in the study 254 preterm infants, whose clinical information met the enrolment criteria. Nineteen out of 48 definitions of EUGR were significantly predictive both for Griffith's Development Quotient (GDQ) and Neurodevelopment Impairment (NDI). Among these, longitudinal definitions appeared to have a higher negative predictive value for NDI than cross-sectional ones. Furthermore, infants with EUGR appeared to have a lower cognitive score than their peers without EUGR. Interpretation: A loss of Zs > 1 SDS in weight and head circumference, calculated from when physiological weight loss is over and identified as soon as possible rather than at discharge, better predicts neurodevelopmental outcomes of preterm infants. Highlights: Only some definitions of EUGR predict neurodevelopmental outcomes. A loss of Zs > 1 SDS identified as soon as possible predicts neurodevelopmental outcome. We suggest assessing EUGR from when physiological weight loss is over. We suggest longitudinally monitoring growth once a week using IG-21 from 27 weeks.